Duns Scotus on God. By Richard Cross. Pp. xii + 289. (Ashgate Studies in the History of Philosophical Theology.) Aldershot and Burlington, VT: Ashgate, 2005. isbn 0 7546 1403 4. Paper £18.99 - Evans, Gillian (The journal of theological studies, 2006)
Duns Scotus made waves in his own time and immediately afterwards and this important study does full justice to the excitement which drove ‘the immediate desire of Scotus's many pupils to create as full a picture as possible’ of his teachings. Richard Cross brings to life the competitive, combative, and argumentative atmosphere of the universities of the late thirteenth and early fourteenth centuries. This leaves us in difficulties, which the author acknowledges, in seeking to establish critical editions of the texts to modern standards, as well as in being sure we have Scotus right., Cross divides the book into two sections, with an appendix on the problem of religious language and the impossibility of talking about God. The first part deals with the existence of the one God.